Susceptibility to Toxoplasmosis and its Risk Factors during Prenatal Care - N Vakil; M Mosayebi; Z Eslamirad (Iran University of Medical Sciences, 2014)
Abstract   Background & Aims: Considering the physical and socio-economic consequences of Toxoplasmosis, survey of the disease in women, before and during pregnancy is very important. The aim of this study was to determine the susceptibility and risk factors of toxoplasmosis among pregnant women by scrutiny of anti-Toxoplasma gondii Immunoglobulins during prenatal care in the healthcare centers in Arak- 2010.   Material & Methods: It was a descriptive, cross-sectional study. A total of 308 women referring to 5 health care centers and during their prenatal care were selected by multistage cluster sampling. Data was collected by an epidemiological questionnaire and diagnostic techniques were done on blood specimens. IgM and IgG anti- T. Gondi were investigated using the immune-enzymatic assay (ELISA) technique. The study data was analyzed by chi-square test using SPSS-PC (v. 11).   Results: The seroprevalence of anti-Toxoplasma IgG and IgM of the women during their prenatal care was 38% and 1/7% respectively. The highest incidence was observed in 20-24 year old women. Significant relationship was seen between total positive cases of IgG and IgM and history of abortion, consumption of undercooked or raw foods (milk, meat and eggs) (P<0/05) . There was no significant relationship between the total positive cases of IgG and IgM and job, level of education, quality of vegetables washing, knowledge about disease, consumption of outdoor foods, and contact with cats.   Discussion: Considering the susceptibility of %64 of women to the disease in the early stages of their pregnancy, reducing the risk of possible complications by health education programs and increasing awareness to the disease and also assessing sensitivity to the disease for married or pregnant women during their prenatal period and doing more extensive research on this issue in the country is recommended.   Received: 14 Dec 2013   Accepted: 22 Feb 2014